Cultivo de Ankistrodesmus gracilis (Reisch) Korsikov (Chlorophyta) em laboratório utilizando meio CHU12 e de macrófita com NPK - Sipauba-Tavares, Lucia Helena [UNESP]; Coral Ibarra, Luiz C.; Fioresi, Tatiana Betioli [UNESP] (Inst Pesca, 2009)
Two different culture media, namely CHU12 and inorganic fertilizer NPK (20-5-20) associated with macrophyte (Eichhornia crassipes) extract, were used to evaluate the development of A. gracilis. Growth rate, development, nutritional value and medium water quality were analyzed. A. gracilis in macrophyte+NPK medium had mean cell density (333x10(5) cells/mL) higher than medium CHU12 (302x10(5) cells/mL). Protein rate (12.52% PS), dry weight (397x10(7) pg/cell) and ashes (4.08x10(7) pg/cell) in A. gracilis was higher (p<0.05) than medium macrophyte+NPK. on the other hand, lipids, carbohydrates and fibers had the same rate (p>0.05) in both media. When hydrological variables in the culture medium of A. gracilis are taken into account, dissolved oxygen and free CO2 alone failed to have any significant difference (p>0.05) between the media employed. A. gracilis in the macrophyte+NPK medium had the same nutritional rate as the commercial medium CHU12, with excellent results for alga growth. Macrophyte medium may be used for large scale alga culture in the feed of fish larvae.
Ankistrodesmus gracilis (Reisch) Korsikov (Chlorophyta) laboratory cultured in CHU12 and macrophyte with NPK media
Keywords: algae; growth; biological aspects; nutritional content